Penusah tana the forgotten struggle - Chiew, Hilary; Chi, Too (Malaysia : Hillary Chiew and Chi Too, 2007)
For over 20 years, Ajang Kiew, a Penan leader, has been setting up blockades to protect his native customary rights land from the instruction of logging companies. To hid dismay, his cries and efforts have fallen on deaf ears. Now, he sets up one final struggle before oil plam tree plantations take over good
Title from container
Subtitle in English
Keywords: Logging -- Sarawak